2016
DOI: 10.1007/s12649-016-9594-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pretreatments of Napier Grass with Deionized Water, Sulfuric Acid and Sodium Hydroxide on Pyrolysis Oil Characteristics

Abstract: The depletion of fossil fuel reserves has led to increasing interest in liquid bio-fuel from renewable biomass. Biomass is a complex organic material consisting of different degrees of cellulose, hemicellulose, lignin, extractives and minerals. Some of the mineral elements tend to retard conversions, yield and selectivity during pyrolysis processing. This study is focused on the extraction of mineral retardants from Napier grass using deionized water, dilute sodium hydroxide and sulfuric acid and subsequent py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 80 publications
3
12
0
Order By: Relevance
“…From the reactor size and carrier gas flowrate reported by the authors, vapor residence was around 1.425 min (85 sec), which is long enough to result to severe secondary cracking of the pyrolysis vapor at such a high temperature. Some classical studies on the pyrolysis of Napier grass have also been reported by our research group recently (Mohammed et al, 2015b;Lim et al, 2015, Mohammed et al, 2016a, 2016b, 2016d, Lim et al, 2016. To date, no study on pyrolysis of Napier grass is available in the literature that deals with collective examination of pyrolysis temperature, heating rate, inert gas flowrate on the products distribution and composition.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…From the reactor size and carrier gas flowrate reported by the authors, vapor residence was around 1.425 min (85 sec), which is long enough to result to severe secondary cracking of the pyrolysis vapor at such a high temperature. Some classical studies on the pyrolysis of Napier grass have also been reported by our research group recently (Mohammed et al, 2015b;Lim et al, 2015, Mohammed et al, 2016a, 2016b, 2016d, Lim et al, 2016. To date, no study on pyrolysis of Napier grass is available in the literature that deals with collective examination of pyrolysis temperature, heating rate, inert gas flowrate on the products distribution and composition.…”
Section: Introductionmentioning
confidence: 80%
“…Lignocellulosic biomass such as forest residues, agro-wastes, energy grasses, aquatic plants, algae, continues to again attention as a suitable alternative energy source. They are non-food materials and consist carbon, which can be converted into high-grade fuel or fuel precursor, biochemicals and other valuable product (Mohammed et al, 2016a;2016b). However, biofuel from these materials is generating another concern.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction time was kept at 60 min (±2 min) after the reaction temperature reaches 600°C. Bio-oil, bio-char and non-condensable yields were determined according to equations 1, 2 and 3 respectively [34]. Bio-oil collected was characterized.…”
Section: Methodsmentioning
confidence: 99%
“…Commonly used techniques include acid treatment [13][14][15][16], alkali treatment [14,17], steam explosion [18], hot-water extraction [19,20], etc. Acid pretreatment as a chemical method is effective in removing minerals from lignocellulosic biomass and can significantly increase the bio-oil yield in thermal pyrolysis [17,21,22]. Previous studies also demonstrated that the removal or passivation of minerals in biomass by mineral acid is an effective method for improving the yields for anhydrosugars from the pyrolysis of biomass [21,23].…”
Section: Levoglucosan (Lg)mentioning
confidence: 99%